Ladies of the Canyons : A League of Extraordinary Women and Their Adventures in the American Southwest - Poling-Kempes, Lesley (Book collections on Project MUSE., 2015)
Educated, restless, and inquisitive, Natalie Curtis, Carol Stanley (founder of Ghost Ranch), Alice Klauber, and Mary Cabot Wheelwright were plucky, intrepid women whose lives were transformed in the first decades of the twentieth century by the people and the landscape of the American Southwest. Part of an influential circle of women that included Louisa Wade Wetherill, Alice Corbin Henderson, Mabel Dodge Luhan, Mary Austin, and Willa Cather, these ladies imagined and created a new home territory, a new society, and a new identity for themselves and for the women who would follow them.